ModelTracer: User-friendly Traceability for the Development of Mechatronic Products. (2016) - Sünnetcioglu, Atakan; Brandenburg, Elisabeth; Rothenburg, Uwe; Stark, Rainer
Abstract: The development of complex mechatronic systems demands an integration of models throughout the virtual product development process. Systems engineering is an approach for enabling the development of successful interdisciplinary products. Traceability, one of the most important aspects of systems engineering, is a method for explicit documentation of logical relationships between development artifacts. In this paper we present a prototype traceability tool, ModelTracer, which aims to reduce the cognitive effort for the creation and maintenance of traceability models in systems engineering.